2015
DOI: 10.3233/fde-150021
|View full text |Cite
|
Sign up to set email alerts
|

A completely transparent, adhesively bonded soda-lime glass block masonry system

Abstract: Abstract.A pioneering, all transparent, self-supporting glass block facade is presented in this paper. Previously realized examples utilize embedded metal components in order to obtain the desired structural performance despite the fact that these elements greatly affect the facade's overall transparency level. Undeniably, the oxymoron 'transparency and strength' remains the prime concern in such applications. In this paper, a new, innovative structural system for glass block facades is described, which demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…Akerboom (2016). A similar concept of glass columns consisting of adhesively bonded cast glass bricks has been tested by Oikonomopoulou et al (2015b) and Felekou (2016).…”
Section: Previous Examples Of All Glass Columnsmentioning
confidence: 99%
“…Akerboom (2016). A similar concept of glass columns consisting of adhesively bonded cast glass bricks has been tested by Oikonomopoulou et al (2015b) and Felekou (2016).…”
Section: Previous Examples Of All Glass Columnsmentioning
confidence: 99%
“…Previous structural and visual tests by Oikonomopoulou et al (2015b) suggested the bonding of the complete contact surface between blocks. The uniform application of the adhesive besides ensuring a homogeneous load distribution, is also essential for maximizing transparency.…”
Section: Bondingmentioning
confidence: 99%
“…Small wall prototypes by Oikonomopoulou et al (2015b), comprising glass elements of different tolerance range, pointed out that a homogeneous bond thicker than 0.3 mm cannot be obtained due to the adhesive's flow properties and medium viscosity. Besides compromising the visual result, inconsistent bonding introduces weaker structural zones.…”
Section: Principles Of the Adhesively Bonded Solid Glass Block Wallmentioning
confidence: 99%
See 2 more Smart Citations